Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Guru (Studi Kasus SDN Kecamatan BandarKabupaten Bener Meriah) - Nur Asnawi Azis; Tri Purwani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of workload and work environment on teacher performance at Public Elementary Schools (SDN) in Bandar District, Bener Meriah Regency. The research method used was quantitative research with a causal approach. The study population consisted of 186 SDN teachers, with a sample of 65 respondents determined using proportionate stratified random sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 31. The results showed that workload had a positive and significant effect on teacher performance with a significance value of 0.001 (<0.05), and that the work environment also had a positive and significant effect on teacher performance with a significance value of 0.001 (<0.05). Simultaneously, workload and work environment had a positive and significant effect on teacher performance with a significance value of 0.001 (<0.05). The coefficient of determination (R²) of 0.570 indicates that 57% of the variation in teacher performance can be explained by workload and work environment, while 43% is influenced by factors outside the study. The conclusion of this study is that workload and work environment are important factors contributing to improved teacher performance. Therefore, proportional workload management and the creation of a conducive work environment need to be a primary focus in efforts to improve the quality of teacher performance at SDN Bandar District, Bener Meriah Regency. Keywords: Workload, Work Environment, Teacher Performance, Elementary School Teachers